2015
DOI: 10.1002/glia.22874
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐induced astrocyte activation is associated with increased amyloid precursor protein expression and processing

Abstract: Cholesterol is essential for maintaining lipid raft integrity and has been regarded as a crucial regulatory factor for amyloidogenesis in Alzheimer's disease (AD). The vast majority of studies on amyloid precursor protein (APP) metabolism and amyloid β-protein (Aβ) production have focused on neurons. The role of astrocytes remains largely unexplored, despite the presence of activated astrocytes in the brains of most patients with AD and in transgenic models of the disease. The role of cholesterol in Aβ product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 68 publications
4
24
0
Order By: Relevance
“…The levels of APP holoproteins, including the isoform containing KPI-domain known to be expressed mostly in astrocytes, are increased time-dependently following U18666A treatment. This is consistent with a recent study which showed that increasing concentrations of cholesterol in the culture media can trigger cholesterol accumulation and elevate APP levels in astrocytes (Avila-Muñoz & Arias, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The levels of APP holoproteins, including the isoform containing KPI-domain known to be expressed mostly in astrocytes, are increased time-dependently following U18666A treatment. This is consistent with a recent study which showed that increasing concentrations of cholesterol in the culture media can trigger cholesterol accumulation and elevate APP levels in astrocytes (Avila-Muñoz & Arias, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The levels of APP holoproteins, including the isoform containing KPI‐domain known to be expressed mostly in astrocytes, are increased time‐dependently following U18666A treatment. This is consistent with a recent study which showed that increasing concentrations of cholesterol in the culture media can trigger cholesterol accumulation and elevate APP levels in astrocytes (Avila‐Muñoz & Arias, ). There is also evidence that APP levels are increased in reactive astrocytes in the affected brain regions of NPC1 knockout mice—characterized by intracellular accumulation of cholesterol in many tissues including the brain (Kodam et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the stimulus‐dependent capacity of reactive astrocytes to express APP (Avila‐Muñoz & Arias, ; Siman, Card, Nelson, & Davis, ) as well as the APP processing enzyme BACE1 (Hartlage‐Rübsamen et al, ) and components of the γ‐secretase complex (Nadler et al, ) indicate a potential astrocytic contribution to amyloid pathology. Indeed, intracellular Abeta was detected in astrocytes of AD cortex (Akiyama et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Arias [36] in isolated astrocytes obtained from brain cortex of 1-to 3-day-old Wistar rats, they found astrocyte activation, An increase on the expression of amyloid precursor protein (APP), and promoted its amyloidogenic processing, and an increase in reactive species oxygen (ROS), a marker of oxidative stress, after treating the culture for 48 h with cholesterol concentrated at 25 or 50 μM. All these parameters measured, including glia activation, resemble features that have been found in postmortem brain tissues obtained from AD patients [37][38][39], but how the consumption of a diet high in cholesterol can contribute to the development of AD?…”
Section: Impact Of a Diet Rich In Cholesterol Or Fat On The Developmementioning
confidence: 99%